Patient reported indicator surveys (PARIS) - Ambrož, Matija (Zdravstveno varstvo, 2024)
the perspectives of patients. Patient Reported Indicator Surveys (PaRIS) is an OECD initiative to measure the outcomes and experiences of people living with chronic conditions, who are managed in primary care. Objectives: To evaluate the feasibility of the methodology employed in the Field Trial of the PaRIS survey in Slovenia and propose adjustments to enhance sampling in the Main Survey. Methods: In 2022, we conducted a cross-sectional observational study in 50 family medicine practices in Slovenia with a target of recruiting 70 patients per practice. We used the Slovenian version of the PaRIS questionnaires, and evaluated sampling and data collection. Results: The sample contained 21 providers (42.0% response rate) and 454 patients (50.7% response rate). The provider sample did not differ from the population characteristics, while the patient sample differed significantly from the patient population. All providers completed the survey online, in 20.9±11.1 minutes and had 1.5±1.5 restarts. Most patients (74.9%) completed the survey online and needed 36.0±22.6 minutes, and the mean number of restarts was 1.4±2.2. Conclusion: Based on the results, we recommend conducting a methodology test for quality assessment studies before initiating the main survey. Legal issues should be addressed and considered early when developing the methodology. It is also necessary to be aware of the feasibility of the study in practice, to avoid a low participation rate.
Keywords: data collection methodology; kakovost zdravstvene oskrbe; metodologije; ocena izkušenj in izidov zdravstvene oskrbe; pacientove izkušnje; patient experience; Patient Reported Indicator Surveys (PaRIS); pPrimary care; primarno zdravstvo; quality of healthcare; zbiranja podatkov